-15g=-19g+13

Simple and best practice solution for -15g=-19g+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15g=-19g+13 equation:


Simplifying
-15g = -19g + 13

Reorder the terms:
-15g = 13 + -19g

Solving
-15g = 13 + -19g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '19g' to each side of the equation.
-15g + 19g = 13 + -19g + 19g

Combine like terms: -15g + 19g = 4g
4g = 13 + -19g + 19g

Combine like terms: -19g + 19g = 0
4g = 13 + 0
4g = 13

Divide each side by '4'.
g = 3.25

Simplifying
g = 3.25

See similar equations:

| 30=200*r*3 | | -(5x+7)-2x=-36.2 | | 23=4a+5 | | 2x+4+x+2x-9=180 | | -37+9x=17+7x | | -45+5x=93-x | | (3p+9)=p+54 | | -2x^2-36x-2y^2-112=0 | | 20-3y-7=-6y-20 | | 25+3x+20=180 | | 12x-43=5x+83 | | 4x^2-5x=1 | | 3(2.5x+7)=6x | | 2x+7=-17-4x | | 3x^2-12x-35=0 | | 4y+12x=24 | | 90=p*0.05*4 | | -28+5x=26+3x | | P-1=43 | | (2a+4b)i+a+5b=15+58i | | -10+8h=10+3h | | 65x-7=18x^2 | | 3z-2=8 | | 12y+6x=36 | | -4+x=42 | | -7-10c=-7c-10 | | 4x-120=-8x+36 | | 11(12+x)= | | y+.25=2 | | 2(x-3)-3(x-4)=1 | | 8+-u=19 | | 4+9b=8b |

Equations solver categories